2020
DOI: 10.21203/rs.3.rs-24212/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Symbiotic microbiome Staphylococcus aureus from human nasal mucus modulates IL-33-mediated type 2 immune responses in allergic nasal mucosa

Abstract: Background: The host-microbial commensalism can shape the innate immune responses in respiratory mucosa and nasal microbiome also modulates front-line immune mechanism in the nasal mucosa. Inhaled allergens encounter the host immune system first in the nasal mucosa, and microbial characteristics of nasal mucus directly impact the mechanisms of initial allergic responses in nasal epithelium. However, the roles of the nasal microbiome in allergic nasal mucosa remain uncertain. We sought to determine the distribu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In the nasal microbiome of patients with AR, S. aureus colonization was significantly predominant, in concert with a high abundance of Staphylococcus spp. Our previous study showed that the distribution of S. aureus was significantly elevated in the nasal mucus of patients with AR, to the point that it constituted more than 20% of the identified nasal microbiome, and S. aureus colonization was most highly abundant relative to the composition of the normal mucus [25]. Thus, we sought to understand the contributions of Staphylococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…In the nasal microbiome of patients with AR, S. aureus colonization was significantly predominant, in concert with a high abundance of Staphylococcus spp. Our previous study showed that the distribution of S. aureus was significantly elevated in the nasal mucus of patients with AR, to the point that it constituted more than 20% of the identified nasal microbiome, and S. aureus colonization was most highly abundant relative to the composition of the normal mucus [25]. Thus, we sought to understand the contributions of Staphylococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the human microbiomes contribute to mucosal and immune system development, as well as to protection from external pathogens. [4][5][6] However, the system consists of trillions of microbiomes.…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that Staphylococcus aureus-derived proteases may induce allergic airway inflammation (23). However, some experimental studies revealed that nasal commensal Staphylococcus aureus from subjects with AR mediated anti-allergic effects (24).…”
Section: Introductionmentioning
confidence: 99%